Hemodynamic effect of outpatient levosimendan infusion assessed daily using the CardioMEMS™ invasive remote monitoring system - Ana Rita Teixeira; Francisco Barbas de Albuquerque; Tiago Pereira-da-Silva; António Valentim Gonçalves; Rita Ilhão Moreira; Ana Teresa Timóteo; João Alves; Sofia Barquinha; Rita Mata; Mariline Dias; Duarte Cacela; Rui Cruz Ferreira (Revista Portuguesa de Cardiologia)
Introduction and Objectives: Levosimendan infusion in the outpatient setting improves the clinical status of heart failure (HF) patients, although its hemodynamic effects are not entirely known. Remote monitoring using the CardioMEMS™ system enables daily assessment of pulmonary artery pressure (PAP) and estimation of cardiac output (CO). We aimed to assess the hemodynamic effects of outpatient levosimendan infusion using CardioMEMS™. Methods: All patients admitted for 6-hour levosimendan infusion (performed every 14 days) and using the CardioMEMS™ remote monitoring system were included in a prospective single-center registry. Clinical and laboratory data were recorded. Systolic, diastolic, and mean PAP, heart rate, CO, and stroke volume (SV) were assessed daily. Results: A total of 25 sessions were performed in three patients. There were no adverse events or significant therapy adjustments. There was a significant reduction in diastolic PAP the day after levosimendan infusion compared to baseline (day prior to infusion) (24.1±4.1 mmHg vs. 21.6±2.9 mmHg, p=0.006). Thereafter, diastolic PAP stabilized and remained significantly lower than baseline up to day 10. There were no significant differences in systolic PAP, mean PAP, heart rate, CO, or SV at any timepoint analyzed, although there was a nonsignificant increase in CO with a peak at day 6. Conclusion: Outpatient levosimendan infusion was associated with an early reduction in diastolic PAP, which was maintained for 10 days. The CardioMEMS™ system may enable a better understanding of outpatient hemodynamics in advanced HF. To our knowledge, there are no published data on this subject. Resumo: Introdução e objetivos: A perfusão de levosimendan em regime de ambulatório melhora o quadro clínico de doentes com insuficiência cardíaca (IC), embora os seus efeitos hemodinâmicos não sejam totalmente conhecidos. A monitorização remota usando o sistema CardioMEMS™ permite a avaliação diária da pressão arterial pulmonar (PAP) e a estimativa do débito cardíaco (DC). O nosso objetivo foi avaliar os efeitos hemodinâmicos da perfusão em ambulatório de levosimendan usando o CardioMEMS™. Métodos: Todos os doentes admitidos em Hospital de Dia para perfusão de levosimendan durante 6 horas (realizada a cada 14 dias) e utilizando concomitantemente o sistema de monitorização remota CardioMEMS™ foram incluídos num registo prospectivo unicêntrico. Os dados clínicos e laboratoriais foram registados. A PAP sistólica, diastólica e média, frequência cardíaca, DC e volume sistólico (VS) foram avaliados diariamente. Resultados: Foram realizadas 25 sessões em 3 doentes. Não houve eventos adversos nem ajustes terapêuticos significativos. Verificou-se uma redução significativa na PAP diastólica no dia seguinte à perfusão de levosimendan comparativamente com o valor basal (dia anterior à perfusão) (24,1±4.1 mmHg versus 21,6±2,9 mmHg, p=0,006). Posteriormente, a PAP diastólica estabilizou e manteve-se significativamente mais baixa em comparação com o valor basal até ao dia 10. Não houve diferenças significativas na PAP sistólica, PAP média, frequência cardíaca, DC ou VS em qualquer ponto de tempo analisado, embora tenha havido um aumento não significativo no DC com pico ao sexto dia. Conclusão: A perfusão em ambulatório de levosimendan associou-se à redução precoce da PAP diastólica, que se manteve por 10 dias. O CardioMEMS™ pode permitir uma melhor compreensão da hemodinâmica em ambulatório na IC avançada. Até onde sabemos, não existem dados publicados sobre este assunto.